Pengembangan Media Interaktif Powerpoint Profil Pelajar Pancasila untuk Siswa Sekolah Dasar - Ranti Ranti; Eddy Noviana; Munjiatun Munjiatun; Guslinda Guslinda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study evaluates the feasibility of the interactive PowerPoint media *Profil Pelajar Pancasila* for 5th-grade elementary school students. Using the Borg & Gall Research and Development (R&D) model, data were collected through surveys, interviews, questionnaires, and validation sheets, analyzed both quantitatively and qualitatively. Media expert validation scored 92, averaging 4.84 (96.84%,